Extinction in Nonautonomous Discrete Lotka-Volterra Competitive System with Pure Delays and Feedback Controls - Ling Zhang; Zhidong Teng; Tailei Zhang; Shujing Gao (Discrete Dynamics in Nature and Society)
The paper discusses a nonautonomous discrete time Lotka-Volterra competitive system with pure delays and feedback controls. New sufficient conditions for which a part of the n-species is driven to extinction are established by using the method of multiple discrete Lyapunov functionals.